Analisis Campur Kode Dalam Video Youtube How I Manage Stress – Maudy Ayunda - Satyaningrum, Retnowati; Khalid, Mohammad (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This study was raised by the researcher's interest in analyzing code mix in the latest video of one of the Indonesian artists and influencers Maudy Ayunda on her personal Youtube page. The video analyzed is a motivational video containing tips and tricks to overcome stress according to Maudy Ayunda which is packaged in the form of a vlog video using Indonesian and English. The purpose of this study is to analyze code mix based on word, baster, phrase, and clause code mix. This research uses a qualitative approach and the method used is descriptive. The data collection techniques used were free listening and note-taking techniques. The data used comes from a video show on Maudy Ayunda's personal channel entitled “how I manage stress-maudy ayunda”. Based on the analysis, there are 37 forms of code mix in the analyzed video. The data is divided into 9 forms of code mix in the form of words, 4 forms of code mix in the form of baster, 10 forms of code mix in the form of phrases and 14 forms of code mix in the form of clauses. The factors that cause code mixing in the video are such as the background of the speaker, the interlocutor and the context of the conversation.